Phytochemistry and Pharmacological Activities of Vernonia amygdalina - Pol, Sagar Laxman; Singh, Pratima; Otia, Mihir; Kothari, Sunil; Mohata, Shubham K; Prakash, Jay (Journal for Research in Applied Sciences and Biotechnology, 2024)
Vernonia amygdalina is a small tree that can grow to a height of ten metres. It is sometimes referred to as bitter leaf due to the fact that its leaves have a bitter bitter flavour and its branches are frail. Although its natural habitat is in tropical Africa, it may be found all over the world in regions that receive an average rainfall of 750–2000 millimetres. These regions include areas that are adjacent to rivers and lakes, as well as forests and grasslands that are located up to an elevation of 2800 metres. The plant is mostly employed as a medicinal herb in the context of traditional medical practices. The plant contains a variety of phytoconstituents, the most important of which are phenol, oxalate, phytates, tannins, flavonoids, cyanogenic glycosides, alkaloids, terpenes, anthraquinone, steroids, coumarins, lignans, xanthones, edotides, sesquiterpenes, and phenol. There are a number of advantages associated with this plant, including its capacity to alleviate fever and pain, as well as its antidiabetic, anti-inflammatory, antioxidant, chemoprotective, and cytotoxic activities.